Пам’яті члена-кореспондента НАН України Б. М. Малиновського (Control systems & computers, 2019)
Малиновський Борис Миколайович – український учений у галузі побудови цифрових керуючих машин та вимірювально-інформаційних систем, член-кореспондент НАН України, доктор технічних наук, професор, заслужений діяч науки та техніки України, лауреат Державної премії України та Премії НАН України імені В.М. Глушкова, академік Міжнародної академії інформатики, кавалер багатьох орденів, медалей та грамот. Borys Malynovsky – Ukrainian scientist in the field of construction of digital control machines and measuring and information systems based on them, Сorresponding member of NAS of Ukraine (since 1969), Doctor of Technical Sciences, Professor, Honored Worker of Science and Technology of Ukraine, laureate of the State Prize of Ukraine, laureate Glushkov Prize of the NAS of Ukraine, International Academy of Informatics, holder of many orders, medals and diplomas.